Working memory training: mechanisms, challenges and implications for the classroom - Song, Jia; MacQuarrie, Sarah; Hennessey, Alexandra (Frontiers in Education, 2023)
There is promising empirical evidence regarding the effect of working memory training for students’ learning. However, this evidence primarily comes from laboratory contexts, which limits understanding of what this training involves and how such knowledge can have value in education. Further, there is considerable heterogeneity across such studies that make it difficult for researchers to determine optimal conditions for working memory training and for educators to implement working memory training that will achieve their educational goal. Grounded in the context of evidence-based practice, this review focuses on applying working memory training in schools to support students’ learning and development, and the need for collaboration between researchers and educators. This review will clarify the theoretical underpinnings of training and transfer and analyse the sources of variation involved in working memory training implementation and outcomes. Building upon this reflection and on existing empirical evidence, this review will consider individual and contextual aspects (e.g., leadership, self-efficacy and school culture) that affect implementation. To support effective implementation within schools, this review discusses the need for a reciprocal researcher-educator partnership to ensure quality implementation of working memory training in the classroom.